The Association between Alexithymia, Depresion, Anxiety and Midas in Migraine patients - Dikmen, Pinar Yalinay; Aysevener, Elif Onur; Kosak, Seda; Aydinlar, Elif Ilgaz; Kocaman, Ayse Sagduyu (SAGE PUBLICATIONS LTD, 2017)
18th International Headache Congress (IHC) of the International-Headache-Society, Vancouver, CANADA, SEP 07-10, 2017